Trimethylamine-N-oxide formation, the bacterial taxa involved and intervention strategies to reduce its concentration in the human body - Ylenia Heinrich-Sanchez; Marius Vital (Annals of Medicine, 2025)
Introduction This study reviews the different steps involved in trimethylamine-N-oxide (TMAO) formation, a gut microbiota (GM)-derived compound that promotes cardiovascular and chronic kidney disease. The formation of TMAO is a metaorganismal process, where trimethylamine (TMA), produced from the dietary precursors betaine, L-carnitine and choline by various members of GM, is absorbed and subsequently oxidized by hepatic flavin-containing monooxygenases before entering the circulation.Results and discussion We provide an updated database on members of GM exhibiting different biochemical pathways and give comprehensive insights into tested as well as hypothetical treatment options to reduce TMAO concentrations in the body. Different angles involving nutrition, TMA-producing bacteria, and their enzymes, as well as host enzymes, are discussed.Conclusion The study underlines the importance to design personalized therapies taking individual features, such as dietary habits and GM composition, into account. Given the multistep nature of TMAO formation, individualized precision multi-target strategies, for instance, reducing dietary precursors in combination with specific modulations of GM limiting growth/activity of TMA-producing bacteria, might be most successful.